2004
DOI: 10.1080/0261976042000211847
|View full text |Cite
|
Sign up to set email alerts
|

The impact of ICT initiatives in Scottish schools: cultural issues

Abstract: At the beginning of a series of ICT initiatives in Scottish schools by the Scottish Executive and again, two years later, a survey of teachers and pupils provided evidence of the impact that these strategic investments had made on the classroom. The findings indicate that while there are innovative and enthusiastic teachers taking advantage of the opportunities afforded, a number of practical and cultural obstacles remained. While practical shortcomings, such as access to suitable hardware and software, might … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
6

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 1 publication
1
29
0
6
Order By: Relevance
“…Several researchers have identified the efficacy of DGBL in classrooms (for example : Clark, Tanner-Smith, & Killingsworth, 2016;Condie & Simpson, 2004;Erhel & Jamet, 2013;Groff, Howells, & Cranmer, 2010;Main & O'Rourke, 2011;Miller & Robertson, 2009, 2011. However, researchers also found scepticism among academics and practitioners that using digital games (particularly those normally associated with leisure activities) is worth the time and financial investment (Bennet, Maton, & Kervin, 2008;Logie & Della Sala, 2010;Sardone & Devlin-Scherer, 2010), especially when more traditional approaches could be just as successful (Prensky, 2001).…”
Section: Literature Review Digital Games Based Learning (Dgbl) In Thementioning
confidence: 99%
“…Several researchers have identified the efficacy of DGBL in classrooms (for example : Clark, Tanner-Smith, & Killingsworth, 2016;Condie & Simpson, 2004;Erhel & Jamet, 2013;Groff, Howells, & Cranmer, 2010;Main & O'Rourke, 2011;Miller & Robertson, 2009, 2011. However, researchers also found scepticism among academics and practitioners that using digital games (particularly those normally associated with leisure activities) is worth the time and financial investment (Bennet, Maton, & Kervin, 2008;Logie & Della Sala, 2010;Sardone & Devlin-Scherer, 2010), especially when more traditional approaches could be just as successful (Prensky, 2001).…”
Section: Literature Review Digital Games Based Learning (Dgbl) In Thementioning
confidence: 99%
“…Additionally, achievement rates were also lower on items that required students to assess the use of different technologies and to think of the social and cultural impact of technological innovations. [1] Using ICT affects the students positively, as it influences the democracy of education, through providing space for the students in choosing the courses they prefer, and sometimes the teacher, resulting in generating feelings of independence and self-confidence, in addition to giving the students the chance to choose what copes with their favorite subjects and their abilities, in addition to the motivation for learning that the use of technology creates inside the classrooms, and widening the students knowledge and critical thinking skills.…”
Section: Teachers' Attitudesmentioning
confidence: 99%
“…Evidence over recent years indicates that, broadly speaking, many teachers use ICT primarily to improve the efficiency of existing tasks. A study of the impact of new technologies on Scottish schools, indicated that both teachers and pupils used a range of technologies and software out of school but while pupils used computers to play, create and explore, teachers were much more likely to use it for work-related tasks such as preparing resources, administration and record-keeping (Condie et al, [24]. In the classroom, use extended to display and presentation using, for example, interactive whiteboards, or research using the Internet.…”
Section: Ict and Creativitymentioning
confidence: 99%